2008
DOI: 10.1128/jb.00123-08
|View full text |Cite
|
Sign up to set email alerts
|

The Xenorhabdus nematophila nilABC Genes Confer the Ability of Xenorhabdus spp. To Colonize Steinernema carpocapsae Nematodes

Abstract: Members of the Steinernema genus of nematodes are colonized mutualistically by members of the Xenorhabdus genus of bacteria. In nature, Steinernema carpocapsae nematodes are always found in association with Xenorhabdus nematophila bacteria. Thus, this interaction, like many microbe-host associations, appears to be species specific. X. nematophila requires the nilA, nilB, and nilC genes to colonize S. carpocapsae. In this work, we showed that of all the Xenorhabdus species examined, only X. nematophila has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 38 publications
4
89
2
Order By: Relevance
“…Here, the genes nilABC are unique to strains infecting the nematode Steinernema carpocapsae but are absent in other Xenorhabdus; heterologous expression of nilABC in the other Xenorhabdus enable their colonization of S. carpocapsae. 40 These findings beg the question as to whether single-locus dependent specificity, such as rscS and nilABC, are extreme outlier cases or, rather, represent a more general basis for host specialization. In Salmonella enterica, a widespread pathogen of mammals and birds, adaptation to hosts is thought to be multifactorial, with both gene gain and loss playing a part.…”
Section: Mechanisms For Maintaining Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the genes nilABC are unique to strains infecting the nematode Steinernema carpocapsae but are absent in other Xenorhabdus; heterologous expression of nilABC in the other Xenorhabdus enable their colonization of S. carpocapsae. 40 These findings beg the question as to whether single-locus dependent specificity, such as rscS and nilABC, are extreme outlier cases or, rather, represent a more general basis for host specialization. In Salmonella enterica, a widespread pathogen of mammals and birds, adaptation to hosts is thought to be multifactorial, with both gene gain and loss playing a part.…”
Section: Mechanisms For Maintaining Specificitymentioning
confidence: 99%
“…A recent gene-swapping study of V. fischeri strains hosted by Australian or Hawaiian Euprymna squids suggested that multifactor-mediated host specificity is not incompatible with single loci of large effect: there may in fact be multiple genes in a genome capable of greatly altering host affinity. 43 These studies demonstrate that horizontal gene transfer, whether by an experimenter or by natural processes (as proposed for rscS 35 and nilABC 40 ), can greatly alter a microbe's host range. In the plant pathogens Xanthomonas and Pseudomonas, type III secretion system effectors are likely important determinants of host specificity.…”
Section: Mechanisms For Maintaining Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic analysis reveals both colonization frequency within a population and localization of bacteria to host tissues 14,16,[19][20][21] . This is an advantage over other methods of monitoring bacteria within nematode populations, such as sonication 22 or grinding 23 , which can provide average levels of colonization, but may not, for example, discriminate populations with a high frequency of low symbiont loads from populations with a low frequency of high symbiont loads.…”
mentioning
confidence: 99%
“…This is an advantage over other methods of monitoring bacteria within nematode populations, such as sonication 22 or grinding 23 , which can provide average levels of colonization, but may not, for example, discriminate populations with a high frequency of low symbiont loads from populations with a low frequency of high symbiont loads. Discriminating the frequency and load of colonizing bacteria can be especially important when screening or characterizing bacterial mutants for colonization phenotypes 21,24 . Indeed, fluorescence microscopy has been used in high throughput screening of bacterial mutants for defects in colonization 17,18 , and is less laborious than other methods, including sonication 22,[25][26][27] and individual nematode dissection 28,29 .…”
mentioning
confidence: 99%